AB1287 DISEASE EVOLUTION OF PRIMARY SJOGREN'S SYNDROME – A LONGITUDINAL STUDY. (June 2019) - Figueiredo, Inês Rego de; Tarn, Jessica; Lendrem, Dennis; Vila, Josephine; Kidd, Elizabeth; Norris, Julie; Hargreaves, Ben; Ng, Wan Fai
Abstract : Background: The natural history of primary Sjogren's syndrome (pSS) remains poorly understood. It has been suggested that the initial presentations may predict the course of disease (1), with gradual reduction of biological activity as measured by serum Immunoglobulins levels (2), while symptoms such as fatigue remaining stable over time(3). Objectives: To evaluate how pSS progresses over time using ESSDAI (Eular Sjögren's Syndrome Disease Activity Index) and the ESSPRI (Eular Sjögren's Syndrome Patient Index), EQ5D-Time trade off (TTO) and Visual Analogue Scale (VAS) of health states. Methods: Routine clinical data from a large single centre cohort in the UK were analysed on patients with ≥3 clinical visits, including up to the 10th visit. Outcomes (ESSDAI/ESSPRI and their component scores, EQ5D-3L and VAS) were analyzed by a random effects linear regression using STATA 14. Results: 346 patients out of 858 included, with a female preponderance of 89%, and median age of 63 years. The median follow up time was 4.9 years, and median disease duration of 12 years. Anti-Ro was positive in 61% and anti-La in 42% of the patients. ESSDAI score decreased 0.1 point per visit (p=0.006). Anti-Ro and anti-La positive patients exhibiting a lower score (p=0.012 and 0.031), and patients with MALT at presentation had a score up to 6 points higher (p= 0.002). Regarding the ESSDAI domains, the constitutional and haematological domains showed increased activity (p-value<0.0001 and 0.018), with Anti-Ro and/or Anti-La patients having higher scores (p <0.0001 and 0.001). In contrast, the glandular, articular and peripheral nervous system domains showed decreases over time (p-values 0.003, 0.006 and <0.0001). ESSPRI score increased 0.05 point/visit (p<0.0001). While Dryness scores remained relatively constant, Pain and Fatigue components of the ESSPRI increased over time (both p<0.0001). Dryness scores were higher in female patients (p=0.04). EQ5D-TTO worsened by 0.03 point/visit (p<0.0001), but the VAS health states remained stable. Conclusion: Our data suggest that symptoms of fatigue and pain as well as health utility worsen over time, whereas different ESSDAI domains showed different trends over time. Longer term follow-up to further understand the natural history of pSS is warranted. References: [1] Skopouli FN, Dafni U, Ioannidis JPA, Moutsopoulos HM. Clinical evolution, and morbidity and mortality of primary Sjogren's syndrome. Semin Arthritis Rheum. 2000;29(5):296–304. [2] Pertovaara M, Pukkala E, Laippala P, Miettinen A, Pasternack A. A longitudinal cohort study of Finnish patients with primary Sjögren's syndrome: Clinical, immunological, and epidemiological aspects. Ann Rheum Dis. 2001;60(5):467–72. [3] Haldorsen K, Bjelland I, Bolstad AI, Jonsson R, Gorgas Brun J. A five-year prospective study of fatigue in primary Sjögren's syndrome. Arthritis Res Ther. 2011;13. Disclosure of Interests: None declared